Common battlefield training for airmen - Manacapilli, Thomas (RAND Project Air Force, 2007)
"Members of Air Force specialties that normally work inside the defended perimeter of a base or deployed location may sometimes have to cross that perimeter. What might seem fairly benign in some locations, such as Germany, would be hazardous in others, such as Iraq. And some initially deployed to a "safe" location may be redeployed to a more hazardous one. While those who routinely go "outside the wire" receive appropriate training, the others historically have not. The Air Force is thus seeking to establish common battlefield airman training (CBAT) and asked RAND Project Air Force to examine the content and resources both for this course and a companion course for non-ground combat personnel. RAND conducted surveys and interviews to determine the kinds of experiences airmen have had "outside the wire" and worked with subject-matter experts to categorize them and suggest appropriate types and amounts of training for them. This report presents the results of these activities."--Publisher's website